Perceptions of the COVID-19 Vaccination Within a Convenience Sample of Sudanese Americans - Jonathan Freese; Fatima Abuzaid; Harlan Sayles; Mujtaba Abdellatif; Nada Fadul (SAGE Publishing, 2024)
Introduction: Sudanese American and other immigrant and refugee communities are at greater risk for exposure to COVID-19. This survey sought to better characterize COVID-19 vaccination practices, motivators, and drivers for hesitancy among Sudanese Americans. Methods: We developed an online, cross-sectional survey in English and Arabic distributed by Sudanese American community leaders in April 2022 with data stored anonymously in REDCap. Inclusion criteria were self-reporting being born within Sudan and living in the US within the last 2 years. Descriptive analysis tested survey responses for possible associations between the primary outcome, self-reported vaccination status, and questions regarding vaccination history, perspectives on vaccination, and demographic characteristics using Fishers Exact and Chi Squared Tests. Results: Of 111 survey responses received, 107 met inclusion criteria. 93% of respondents reported COVID-19 vaccine uptake with the primary motivation to protect oneself from disease. The most cited reason for vaccine hesitancy was belief it had not been studied enough. The group that reported vaccination had higher levels of education (.032) and were more likely to perceive that COVID-19 vaccinations were able to reduce spread (.001), decrease severe outcomes (.004), and benefits outweighing their risks (.004). Discussion and Conclusions: This survey population of Sudanese Americans demonstrated high levels of vaccine uptake (93%), far greater than either the corresponding US (78%) or Sudanese population (15%). It is likely that high levels of educational attainment moderated vaccine uptake, though our survey may not have had the power to fully evaluate vaccine hesitancy.